2013
DOI: 10.1111/sms.12057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slope and footwear on running economy and kinematics

Abstract: Lower energy cost of running (Cr) has been reported when wearing minimal (MS) vs traditional shoes (TS) on level terrain, but the effect of slope on this difference is unknown. The aim of this study was to compare Cr, physiological, and kinematic variables from running in MS and TS on different slope conditions. Fourteen men (23.4 ± 4.4 years; 177.5 ± 5.2 cm; 69.5 ± 5.3 kg) ran 14 5-min trials in a randomized sequence at 10 km/h on a treadmill. Subjects ran once wearing MS and once wearing TS on seven slopes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 31 publications
1
42
1
Order By: Relevance
“…When shoe mass and running gait were not controlled for between minimalist shoes and conventional running shoes, the beneficial effect of minimalist shoes on running economy increased (SMD = 0.12-0.79) [6,25,27] ( Table 2). This larger beneficial effect could be partly explained by the reduction in shoe mass associated with minimalist shoes compared with conventional shoes but could also be due to changes in foot strike and cadence that have previously been associated with running in a minimalist shoe [6,27,50].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When shoe mass and running gait were not controlled for between minimalist shoes and conventional running shoes, the beneficial effect of minimalist shoes on running economy increased (SMD = 0.12-0.79) [6,25,27] ( Table 2). This larger beneficial effect could be partly explained by the reduction in shoe mass associated with minimalist shoes compared with conventional shoes but could also be due to changes in foot strike and cadence that have previously been associated with running in a minimalist shoe [6,27,50].…”
Section: Discussionmentioning
confidence: 97%
“…All studies expressed oxygen uptake (VO 2 ) relative to body mass. Fifteen studies [2, 6, 7, 9-14, 21, 23, 24, 26-28] expressed VO 2 relative to time, three studies [5,15,25] expressed VO 2 relative to distance and two studies [22,28] converted VO 2 to caloric expenditure. The unit of measure chosen to assess running economy did not appear to affect study findings ( Table 2).…”
Section: Study Outcomesmentioning
confidence: 99%
“…Rather, the findings of the majority of studies are based on results from acute interventions or using previously habituated barefoot or minimalist runners (Divert et al, 2008;Hanson et al, 2011;Lussiana et al, 2013;Perl et al, 2012;Squadrone & Gallozzi, 2009). Recently published data by our research group observed significant improvements in running economy (8.09%) following a four week familiarization to minimalist footwear (MFW) with no gait-retraining, when compared with conventional running shoes (CRS) .…”
Section: Introductionmentioning
confidence: 98%
“…In a homogenous group of runners, running economy (RE) has been considered a strong predictor of endurance performance (Lucia, Esteve-Lanao, Olivan, Gomez-Gallego, & Foster, 2006). With regard to footwear, several studies have reported significant differences in RE between barefoot or minimalist footwear when compared to conventional footwear (Divert et al, 2008;Lussiana, Fabre, Hébert-Losier, & Mourot, 2013;Perl et al, 2012;Squadrone & Gallozzi, 2009; and so it appears that changing footwear may be a means to influence performance.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, running in minimalist shoes may promote performance by utilising less amount of oxygen than shod running (Cheung & Ngai, 2015). Better running performance could be a result of lower shoe mass, which was found to correlate with the cost of running (Franz, Wierzbinski, & Kram, 2012;Lussiana, Fabre, Hébert-Losier, & Mourot, 2013).…”
Section: Introductionmentioning
confidence: 88%